Pinocchio - Toro, Guillermo del, 1964-; Gustafson, Mark; Henson, Lisa, 1960-; Ungar, Gary; Bulkley, Alexander; Campodonico, Corey; McHale, Pat; Robbins, Matthew; McGregor, Ewan, 1971-; Bradley, David, 1942-; Mann, Gregory, 2009-; Gorman, Burn, 1974-; et al. (New York The Criterion Collection, 2023)
A classic tale is reborn through the inspired imagination of cinematic dream-weaver Guillermo del Toro, directing alongside Mark Gustafson. Realized through boundary-pushing, breathtakingly intricate stop-motion animation, this dark rendering of the fable of the puppet boy and his maker, which won the Academy Award for Best Animated Feature, daringly transfers the story to Fascist Italy, where the irrepressible Pinocchio gradually learns what it means to be human through his experiences of war, death, and sacrifice. This version of the story imbues the oft-told tale with a bold new resonance about living with courage and compassion.
Disc 1. Movie -- disc 2. special features.
Based on the book Pinocchio written by Carlo Collodi.
Originally released as a motion picture in 2022.
Accompanying booklet includes essays by film critic Matt Zoller Seitz and author Cornelia Funke.
Special features: Handcarved cinema: a new documentary featuring del Toro, Gustafson, and cast and crew, including the film's puppet creators, production designers, and animation supervisor; Directing stop-motion: a new program featuring del Toro and Gustafson; Eight rules of animation: new program on the principles of animation that informed the film's production; New conversation between del Toro and film critic Farran Smith Nehme; Crafting Pinocchio for MOMA: new interview with curator Ron Magliozzi on The Museum of Modern Art's 2022 exhibition devoted to the film; Panel discussion featuring del Toro, Gustafson, production designer Guy Davis, composer Alexandre Desplay, and sound designer Scott Martin Gershin, moderated by filmmaker James Cameron; Conversation among del Toro, Gustafson, and author Neil Gaiman; in booklet, ezssays by film critic Matt Zoller Seitz and author Cornelia Funke.
Director of photography, Frank Passingham ; editors, Ken Schretzmann, Holly Klein ; music, Alexandre Desplat.
Ewan McGregor, David Bradley, Gregory Mann, Burn Gorman, Ron Perlman, John Turturro, Finn Wolfhard, Cate Blanchett, Tim Blake Nelson, Christoph Waltz, Tilda Swinton.
Keywords: Pinocchio -- (Fictitious character) -- Drama; Collodi, Carlo, -- 1826-1890.; 1918-1945; Puppets -- Drama; Fathers and sons -- Drama; Wood-carvers -- Drama; Fairy tales -- Film adaptations; Social conditions; Italy -- Social conditions -- 1918-1945 -- Drama; Fantasy films; Stop-motion animation films; Animated films; Feature films; Film adaptations; Video recordings for the hearing impaired; Video recordings for people with visual disabilities